Familiar places — (Re)creating “home”: an exegesis - Papas, Maria (Curtin University, 2009)
My thesis — a novel and an accompanying exegesis — addresses the question: what is ‘home’? What are the ways in which it has been and can be understood? And in particular, how can it be represented in narrative fiction so as to take into account its many intricate facets? Framed by my understanding of the relationship between mental inscapes and outward landscapes, I propose that ‘home’ is not so much a geographical space as it is an interpretation of that space, and that, in prose, this interpretation is based on the subjective viewpoint of a narrative focaliser.This said, in my creative practice I explore experiences of ‘home’ through two alternate focalisations. I represent ‘home’ in several ways: as the tension point between nurture and neglect; as a space of transience and fluidity; as an experience of familiarity; and as part of the everyday process of the creation of self. Drawing upon the landscape, culture and community of the places I have lived in — Bunbury, Albany and Perth — and the years I have spent traversing the roads within and between, this is a novel in which the sense of home (or the homelike moment) is constructed out of movement, communication and sociality. This is a novel in which ‘home’ is not just a place; it is an activity.Relative to my creative practice, my exegesis details how the construction of my novel was based on a triangulate relationship between personal experience, theoretical readings and the exemplar of fiction. Each chapter examines ‘home’ from a certain theoretical point of view, and in turn the representational applications of these points of view are studied via a close reading of Thea Astley’s A Descant for Gossips and in my own work. Finally, it is this understanding — point of view, perception, focalisation — that forms the basis of both my creative and theoretical work.